2021
DOI: 10.3390/jcm10225425
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Health Status and Relative Handgrip Strength in 11,337 Korean

Abstract: Grip strength is a simple indicator of physical strength and is closely associated with systemic health. Conversely, oral health has also been reported to have an important association with systemic health. The present study aimed to assess the effect of oral health status on relative handgrip strength. The data pertaining to 11,337 participants were obtained by means of the seventh Korea National Health and Nutrition Survey (2016 to 2018). Oral health status was evaluated on the basis of the presence of perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…A recent cross-sectional study that include participants from the Korea National Health and Nutrition Examination Survey (KNHANES) database indicates that after adjustment for the risk factors of periodontitis, the likelihood of periodontitis decreased as the level of handgrip strength increased (OR = 0.986 [0.974, 0.999], p = 0.030) [26]. Ji-Eun Kim also revealed a signi cant association in the group of patients with periodontal disease (OR = 1.69 [1.51, 1.89]) [12]. In addition, it is the men in the youngest age group (30-49 years) showed the strongest association between PD and low hand grip strength [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent cross-sectional study that include participants from the Korea National Health and Nutrition Examination Survey (KNHANES) database indicates that after adjustment for the risk factors of periodontitis, the likelihood of periodontitis decreased as the level of handgrip strength increased (OR = 0.986 [0.974, 0.999], p = 0.030) [26]. Ji-Eun Kim also revealed a signi cant association in the group of patients with periodontal disease (OR = 1.69 [1.51, 1.89]) [12]. In addition, it is the men in the youngest age group (30-49 years) showed the strongest association between PD and low hand grip strength [27].…”
Section: Discussionmentioning
confidence: 99%
“…The hand grip strength test is a simple and effective way of measuring muscle strength [9]. Considerable epidemiological evidence shows a signi cant association between PD and low handgrip strength [10][11][12]. However, there is no connection between hand grip strength and PD when adjusted for several variables [13].With inherent limitations of conventional observational studies, including small sample sizes and confounding and reverse causality, the causal relationship between PD and hand grip strength has yet to be established, which is extremely important and could improve our present understanding of PD and low hand grip strength pathogeneses.…”
Section: Introductionmentioning
confidence: 99%
“…However, in another study, it was reported that sarcopenia as a diagnostic criterion for handgrip strength and present teeth in participants aged over 80 years were related before adjusted [ 33 ]. Another study also reported an association between present teeth and low relative handgrip strength as continuous and categorical variables in adults [ 34 ]. This is in agreement with the results of our study, which suggests that oral health status, defined as having less than 20 teeth, may increase the risk of low muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto et al [ 37 ] suggested that older adults aged 80 years or above who showed high handgrip strength had more teeth than did those with low handgrip strength. In addition, cross-sectional studies among adults aged ≥19 years reported that people with low handgrip strength showed poorer oral health behaviors, including tooth brushing [ 38 , 39 ]. Therefore, considering previous studies and our findings, we infer that reduced handgrip strength has a direct and indirect adverse effect on the ability to perform daily oral care in adults aged ≥30 years and eventually contributes to developing periodontal inflammation over a prolonged period.…”
Section: Discussionmentioning
confidence: 99%